Relations Between Stress and Deformation of Ice, Considering the Time Factor (Zavisimost Mezhdu Napriazheniem i Deformatsiei l'da s Uchetom Faktora Vremeni) - Vyalov,S. S.; Chernigov,V. A. (1975)
The stress deformation relationship is given by the exponential function, the parameters of which are dependent of the rate of loading. During compression the density of ice and its modulus of dynamic elasticity increase. Rules 1 and 2 are valid until a deformation limit epsilon sub T is reached; after which intensive flow occurs and the modulus of dynamic elasticity sharpely decreases. The limiting deformation epsilon sub T is load-rate and load-time independent and is constant for a given ice sample. However, the limiting compression epsilon sub pr is a variable; it is rate and time dependent. The limiting deformation epsilon sub T is a criterion for ice stability, characterizing an intensively progressing flow followed by pulverization, occurrence of microocracks and deterioration of the ice crystals. Draft trans. of Sovetskaya Antarkticheskaya Ekspeditsiya. Trudy, n10 p249-254 1960.